Development and challenges of agritourism in Malaysia - Mazlan, Norida; Juraimi, Abdul Shukor (International Society for Southeast Asian Agricultural Sciences, 2014)
Agritourism started in 1991 in Malaysia as one of tourism diversity activity to improve country account balance. It was included in Sixth Malaysia Plan (1991-1995) where Malaysia's national tourism plan was formulated to increase tourist arrival into the country. This plan was successfully implemented and Malaysia has been in top 10 countries with highest number of international tourist arrival since 2006. At the beginning, most of agritourism places are usually in the form of introducing plants and animal, and its only known to local tourist and cater for the team building and recreation activities. With the support from governments sectors in marketing and promoting the tourism package, there are many types of activities and packages has been developed and introduced to attract visitors which includes farm stay, pick you own, farm animals, fishing and homestay. The agritourism activities are runs by privates sectors and also local communities. As many of agritourism activities are relate to rural areas, the involvement of local village communities is important to ensure the success of a program and to get returns from the investment. One of such program is Homestay which has successful program to increase the farmers/fisherman income and at the same time introduced the local cultures to visitors. Although tourism has become the second source of income from foreign exchange in the country, the percentage of agritourism contribution is still low compared to other tourism sectors.